Coreference and parallelism. Issue 3 (2nd April 2021) - Hall, Kathleen; Yoshida, Masaya
ABSTRACT: Previous studies have demonstrated a reliable effect of parallelism in a variety of domains. These studies have suggested that parallelism is preferred during both production and comprehension, and that parallelism can result in facilitation during sentence processing. There is, however, some debate about whether such effects are truly limited to coordination. In both coordinate and subordinate environments we examined whether parallelism affects pronoun resolution, and furthermore investigated whether distance between a pronoun and an antecedent (locality) affects the retrieval process. Two experiments, each consisting of an offline forced choice task as well as an eye tracking task, indicated that both locality and parallelism influence the pronoun resolution process in both coordinate and subordinate contexts. These findings are discussed in light of popular retrieval models.